2020
DOI: 10.1021/acs.energyfuels.0c02268
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of Kerogens with Different Maturities

Abstract: The thermogenic transformation of kerogen into hydrocarbons accompanies the development of a pore network within the kerogen that serves as gas storage locations both in pore space and the surface area for adsorbed gas with source rocks. Therefore, the successful recovery of gas from these rocks depends on the accessible surface area, surface properties, and interconnectivity of the pore system. These parameters can be difficult to determine because of the nanoscale of the structures within source rocks. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…22−24 Bazilevskaya et al 25 found that over 50% pores in shale are smaller than 20 nm in size. Chiang et al 26 revealed that kerogen with higher maturity has a larger pore volume and a larger contactable specific surface area. Garum et al 27 reconstructed a microscopic three-dimensional shale structure and found that the small and large pores form a highly connected pore network together.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22−24 Bazilevskaya et al 25 found that over 50% pores in shale are smaller than 20 nm in size. Chiang et al 26 revealed that kerogen with higher maturity has a larger pore volume and a larger contactable specific surface area. Garum et al 27 reconstructed a microscopic three-dimensional shale structure and found that the small and large pores form a highly connected pore network together.…”
Section: Introductionmentioning
confidence: 99%
“…The pore structures have been the focus in many studies. Nitrogen adsorption, , mercury intrusion porosimetry, , and helium ion microscopy have been used to characterize the pore structure and connectivity of kerogen, revealing that kerogen is abundant of micro- (<2 nm), meso- (2–50 nm), and macro-pores (>50 nm). Bazilevskaya et al found that over 50% pores in shale are smaller than 20 nm in size. Chiang et al revealed that kerogen with higher maturity has a larger pore volume and a larger contactable specific surface area. Garum et al reconstructed a microscopic three-dimensional shale structure and found that the small and large pores form a highly connected pore network together.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liu et al developed a method to quantify surface heterogeneity of porous materials. , This method also assumes that all of the pore are accessible to external fluids because it relies on contrast variation. By variation of the SLDs of the fluid, such as increasing the pressure of CD 4 , several scattering curves are obtained.…”
Section: Discussionmentioning
confidence: 99%
“…When the experimental data are fitted with IR (ρ f ), a surface-averaged SLD and a normalized mean square variation of the SLD (Δ H 2 ) are obtained. A smaller Δ H means that surface chemistry over the entire interface in the material is more homogeneous. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation